2014
DOI: 10.1021/mp5006195
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Therapeutic Index in Cancer Therapy by Using Antibody–Drug Conjugates Designed with a Moderately Cytotoxic Drug

Abstract: The antibody-drug conjugate (ADC), IMMU-130, of the moderately cytotoxic topoisomerase I inhibitor, SN-38, and the CEACAM5-targeted humanized antibody (mAb), labetuzumab, was evaluated in model systems of human colon carcinoma and in phase I clinical trials of heavily pretreated patients with metastatic colorectal cancer. The conjugate, designed with a near-homogeneous drug substitution of 7-8 SN-38/mAb and with a linker that released 50% of the drug in ∼20 h, showed significant antitumor effects compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Likewise, in A-375 melanoma, there were no changes in p-ERK levels mediated by either IMMU-114 or IMMU-140. This is consistent with reports that in solid tumors, including melanoma, HLA-DR signaling is through phosphorylation of p125 focal adhesion kinase and not ERK (2,30). In AML, it has been suggested that increased expression of Bcl-2 proteins, in particular Mcl-1, act to attenuate apoptosis (35,36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, in A-375 melanoma, there were no changes in p-ERK levels mediated by either IMMU-114 or IMMU-140. This is consistent with reports that in solid tumors, including melanoma, HLA-DR signaling is through phosphorylation of p125 focal adhesion kinase and not ERK (2,30). In AML, it has been suggested that increased expression of Bcl-2 proteins, in particular Mcl-1, act to attenuate apoptosis (35,36).…”
Section: Discussionsupporting
confidence: 91%
“…The moderately stable linker in these unconventional ADCs enables the drug to be released in the acidic pH of tumor microenvironment, while internalization further increases the drug's bioavailability. These design features, while not amenable to showing specificity in vitro, have resulted in encouraging clinical activity of other ADCs (anti-Trop-2 ADC, anti-CEACAM5 ADC) in solid cancer therapies (14)(15)(16)(17)30). In particular, the same conjugation method has been used to create an anti-Trop-2 SN-38-ADC (sacituzumab govitecan, IMMU-132) that targets Trop-2 on solid tumors, and likewise has been shown to be superior to parental antibody both in vitro and in vivo (18,19,31).…”
Section: Discussionmentioning
confidence: 99%
“…Payload internalization was seen but no cytotoxicity data was disclosed. A similar 'bispecific/bifunctional capture idea is Immunomedics' Dock and Lock approach, which is based on the non-covalent interaction between the regulatory subunit of cAMP-dependent protein kinase (dimerization and docking domain) and a kinase anchor domain (AD), which assembles into a covalently locked complex [75].…”
Section: Fusion Proteinsmentioning
confidence: 99%
“…All these results indicate, not surprisingly, that these initial leads in Table-1 are far from optimal, and are potential candidates for further development by structure-guided design and chemical synthesis. Since some of these initial leads exhibit varying degrees of cytotoxicity against the normal cells that we tested against (i.e., MCF10A), they and their derivatives are also excellent candidates for targeted delivery by antibody-conjugation 33 or nanoparticles 34 to deliver the inhibitors to pancreatic cancer cells with high specificity and with minimal effects on normal cells.…”
mentioning
confidence: 99%